The Impact of Digital Literacy in the Use of E-Court on the Fulfillment of Access to Justice at the Tanjung Karang Religious Court Class IA - Tariska Devi; Firmansyah Firmansyah; Agus Salim Ferliadi (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2026)
This study analyzes the impact of digital literacy on the use of the e-Court system at the Tanjung Karang Class IA Religious Court from the perspective of access to justice. The central problem examined is the gap between the availability of the e-Court system and the actual capacity of the public to use it. Three aspects are examined: administrative efficiency, digital literacy challenges, and implications for access to justice. A qualitative juridical-empirical method was applied through in-depth interviews with judges, PTSP officers, e-Court administrators, lawyers, and justice seekers, supported by direct observation and source triangulation. Findings show that e-Court significantly improves administrative efficiency but has not yet accelerated substantive case resolution. Digital literacy gaps remain a primary barrier, especially for the elderly, less-educated populations, and those without digital devices. Consequently, digitalization expands availability of court services but does not yet guarantee equal capacity to use them. Fulfilling access to justice in a digital context requires hybrid services, PTSP digital assistance, digital literacy strengthening, and more user-friendly system design for vulnerable groups.